Understanding Imitatio Dei in the Holiness Source - Hosle, Paul K. (Vetus Testamentum, 2023)
This essay concerns the vexed question of imitatio Dei in the Holiness Code (Lev 17–26) and, to a minor degree, other Holiness (H) traditions in the Pentateuch. I argue that H possesses a robust theology of imitatio Dei, but that the specific form that this imitation takes requires further clarification. Conceptually, I distinguish between the imitandum (i.e., that which is to be imitated) and the imitatio (i.e., the act of imitating). I argue that the imitandum is holiness understood as a quality proper to the deity that is irreducible to a code of conduct, but that this does not vitiate the applicability of the concept of imitatio Dei. On the level of the imitatio, I emphasize the irreducibly social nature of the imitatio, as well as its theocentric logic of justification. Within a typology of imitational structures, H represents an interesting case where both the imitandum and imitatio are heteronomously determined by the external demand of the deity and where the impulse of private, subjective moral growth plays a negligible role.